1988
DOI: 10.1172/jci113780
|View full text |Cite
|
Sign up to set email alerts
|

Local extrahepatic expression of complement genes C3, factor B, C2, and C4 is increased in murine lupus nephritis.

Abstract: Systemic lupus erythematosus (SLE) is associated with the presence of complement proteins and immune complexes in affected organs. Since complement proteins are synthesized in hepatic and extrahepatic sites, we studied a murine model of SLE to ascertain the relative importance of local and humoral (liver) synthesis of complement. C3, C4, and C2 mRNA increase in kidney coincident with the development of nephritis in the MRL lpr/lpr mouse, a strain that spontaneously develops SLE. Two factor B messenger RNA tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
90
0
2

Year Published

1993
1993
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(93 citation statements)
references
References 32 publications
1
90
0
2
Order By: Relevance
“…However, we do know that in hCRPtg/BW mice, there is a virtual absence of immune complex deposition in the renal cortex and an increased accumulation of dense deposits in the glomerular mesangium, and we think this is informative. As we demonstrated here for C3, other complement proteins are also expressed by the renal epithelium in murine lupus nephritis (33)(34)(35). CRP is known to activate complement via the classical pathway (14), and the classical pathway plays an important physiologic role by preventing the formation of immune complexes (36).…”
Section: Discussionsupporting
confidence: 57%
“…However, we do know that in hCRPtg/BW mice, there is a virtual absence of immune complex deposition in the renal cortex and an increased accumulation of dense deposits in the glomerular mesangium, and we think this is informative. As we demonstrated here for C3, other complement proteins are also expressed by the renal epithelium in murine lupus nephritis (33)(34)(35). CRP is known to activate complement via the classical pathway (14), and the classical pathway plays an important physiologic role by preventing the formation of immune complexes (36).…”
Section: Discussionsupporting
confidence: 57%
“…Our earlier studies with Crry demonstrated that complement activation was critical for the pathology in lupus cerebritis [5]. Furthermore, fB, an important component of the alternative pathway, was increased in MRL/lpr mice [8], suggesting a role for this protein in lupus. Therefore, we examined the role of the alternative pathway in lupus cerebritis by studying MRL/lpr mice in the presence and absence of fB.…”
Section: Discussionmentioning
confidence: 92%
“…Complement can be activated through classical, alternative and lectin pathways. Complement factor B (fB) is a key protein required for the activation of the alternative pathway [6] and is increased in circulation and in tissues of lupus mice [7][8][9]. In addition, fB solubilizes immune complexes, inhibits proliferation, acts as a B cell growth factor and activates monocytes 15].…”
Section: Introductionmentioning
confidence: 99%
“…It is now recognized that the kidney itself is a significant source of complement components. 5 Recent experimental work has suggested that such local synthesis of complement has great influence on local tissue injury in the transplanted kidney 6 and that local production in the kidney, for example of the pivotal component C3, which links the activation and terminal cascades of complement, is increased in response to I/R injury. 7 In addition, ischemia/reperfusion injury and its contributory factors have a serious negative impact on acute rejection and the long-term results in clinical transplantation.…”
mentioning
confidence: 99%